Impacts of topography on sediment discharge in Loess Plateau, China. (10th June 2017) - Cheng, N.N.; He, H.M.; Yang, S.Y.; Lu, Y.J.; Jing, Z.W.
Abstract: Geomorphologic characteristics of a basin affect mass movement, water and sediment transport. The purpose of this study is to examine coupling relationship between topography and soil erosion in Loess Plateau during past 50 years (1960–2011). We firstly describe the distribution patterns of topographic characteristics and sediment discharge in specific river basins. By using mathematical methods (PCA method, linear regression and ANOVA analysis) and topographic variables, we build a comprehensive index – Erosion Topography Index (ETI). According to the research, the following findings are obtained. Firstly, average sediment discharge varies from 0.13 × 10 8 t to 7.56 × 10 8 t along the Yellow River from the upper-stream to down-stream. The sediment discharge of this region decreased 60%–90% since the year of 1980, and decrease tendency is more obvious after the year 2000 compared to the period of 1980–2011. Secondly, topographic characteristics and the Erosion Topography Index has similar distribution pattern. Thirdly, there is no significant linear correlation between ETI and all four sediment discharge variables (average sediment, total sediment, sediment of 1980–2011, and sediment of 2000–2011), but there are significant positive linear correlations ( p < 0.05) between ETI and each sediment discharge variable. Furthermore, the correlation between ETI and sediment of 2000–2011 is stronger ( p = 0.035) than other variables, and the gradient coefficient of them is higher ( k = 0.667) than other variables too. Except the topographic characteristics, the vegetation coverage and human activities should be other factors that can influence the variations of sediment discharge in Loss Plateau.